A Comparison of Coping Strategies in Iranian Female Victims of Different Types of Intimate Partner Violence - Kasaeinia, Simin; Hajian, Sepideh; Ahmadi Doulabi, Mahbobeh (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Spouse abuse is defined as physical, sexual, and psychological-emotional violence committed by a spouse against his wife that is a widely variable phenomenon. The present study was conducted to compare coping strategies for stress in Iranian female victims of spouse abuse of different types in the city of Ilam. Methods: The present cross-sectional descriptive study was conducted on 150 females with an experience of spouse abuse during the one-year leading up to the study, selected through convenience sampling. The study tools included the World Health Organization Violence against Women instrument and the Endler and Parker Coping Inventory for Stressful Situations. Data were analyzed using the SPSS-22 software. Results: All of the participants had experienced at least one type of psychological violence (100%). Some of them had also experienced physical (94%) and sexual (67.3%) violence in the past year. Emotion-focused strategies were the dominant style used by most of the females (48%) in coping with stress. Certain demographic variables, such as the couple›s low literacy, were associated with emotion-focused and avoidance coping strategies. The use of problem-focused strategies increased significantly with household size (r = 0.17 and P = 0.039). One-way Analysis of Variance (ANOVA) showed that physical violence was associated with an increase in avoidance strategies and sexual and psychological violence with an increase in emotion-focused strategies. The results of the multivariate linear regression showed that only sexual violence could predict emotion-focused strategies (β = 0.216 and P = 0.01). Conclusions: Given the high prevalence of spouse abuse, teaching certain life skills, such as problem-solving and alternative problem-focused behaviors instead of focusing on emotion and stress could be effective in coping with stressful life situations, help improve interpersonal relationships, and prevent harm caused by violence.